Project implementation success and Change Management practices in Malaysian Government-linked companies (GLCs) - Salem Basamh, Saeed; Huq, Md Najibul; Ahmad Dahlan, Abdul Rahman (International Foundation for Research and Development (IFRD), 2013)
The purpose of this research is to address the practices of project change management in the context of Government-Linked Companies (GLCs) in Malaysia, focusing on Project Managers (PMs), Project Team Members (PTMs), Change Managers (CMs) and any other Top Managers involvement in a project. Also, checking the validity of a number of critical success factors from Project Implementation Profile (PIP) perspective in the context of GLCs in Malaysia. PIP is a comprehensive managerial tool that was introduced by Pinto and Slevin. Later, Belout and Gauvereau have enhanced and re-tested it in their study. Government-linked companies were previously government agencies or public enterprises established to provide services for social purposes. The Malaysian Government considers the importance of the GLCs' role. Critical success factors (or CSFs) are the actions and processes that can be controlled or affected by management to achieve the goals set by an organization. Many studies has been conducted on Malaysian government-linked companies, but few focused on examining the validity of the critical success factors in these GLCs where these factors will lead to successful project implementation, integrating change management.